2022
DOI: 10.4103/jfmpc.jfmpc_528_22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social networking services on academic performance and self-esteem: A cross-sectional study among medical students

Abstract: Background: Social networking services (SNS) are a subcategory of social media that provide a useful tool for an individual’s practical life and social relations. Since the impact of SNS on students’ lives is a relatively neglected topic, we aimed to investigate the effect of social media on academic performance and self-esteem. Methods: A cross-sectional study was conducted with 373 medical students distributed across different academic years. Data was collected and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, no significant relationship was found between the students’ GPA and the time spent on social media. 25 A study done among medical students in Riyadh, KSA found no significant association between GPA and the frequency of daily social media use. 12 Also, a study among second-year medical students in Iraq showed that time spent on social media does not affect their academic performance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, no significant relationship was found between the students’ GPA and the time spent on social media. 25 A study done among medical students in Riyadh, KSA found no significant association between GPA and the frequency of daily social media use. 12 Also, a study among second-year medical students in Iraq showed that time spent on social media does not affect their academic performance.…”
Section: Discussionmentioning
confidence: 97%
“…However, no significant relationship was found between the students' GPA and the time spent on social media. 25 A study done among medical students in Riyadh, KSA found no significant association between GPA and the frequency of daily social media use. 12 Also, a study https://doi.org/10.2147/AMEP.S434150…”
Section: Discussionmentioning
confidence: 97%
“…The minimum required sample size for this study was 361 students according to the sample size equation calculation for cross-sectional studies (17) . Considering that social media can affect 37.5% of students' academic performance from a previous study (18) . Inclusion criteria include all students from colleges of Wasit University who agreed to participate and fill out the questionnaire aged above 18 years old.…”
Section: Methodsmentioning
confidence: 97%